Integrating healthcare quality concerns into a competition law analysis : mission impossible? - Stavroulaki, Theodosia (European University Institute, 2017)
Healthcare markets have started being created in Europe. Indeed, some European countries, such as the UK and the Netherlands, have started adopting the choice and competition model for healthcare delivery. Taking as a starting point that as health systems in Europe move towards market driven healthcare delivery, the application of competition law in these systems will increase, the goal of this doctoral thesis is (a) to identify some of the competition problems that may be raised in light of the reality that especially in hospital and medical markets the pursuit of competition and the pursuit of essential dimensions of healthcare quality may inevitably clash (b) to demonstrate that competition authorities would be unable to address some of these competition problems if they did not pose and address a fundamental question first: how should we define and assess quality in healthcare? How should we take healthcare quality into account in the context of a competition analysis? In delving into these questions, this doctoral thesis explores how the notion of healthcare quality is defined from antitrust, health policy and medicine perspectives and identifies three different models under which competition authorities may actually assess how a specific anticompetitive agreement or hospital merger may impact on healthcare quality. These are: (a) the US market approach under which competition authorities may define quality in healthcare strictly as choice, variety, competition and innovation (b) the European approach under which competition authorities may extend the notion of consumer welfare in healthcare so that it encompasses not only the notions of efficiency, choice and innovation, but also the wider objectives and values European health systems in fact pursue (c) the UK model under which competition authorities may cooperate with health authorities when they assess the impact of a specific transaction on healthcare quality. The thesis identifies the main merits and shortcomings of these models and emphasizes that what is crucial for the adoption of a holistic approach to healthcare quality is not only the model under which healthcare quality is actually integrated into a competition analysis but also competition authorities’ commitment to protect all dimensions of this notion.
Keywords: European Union countries; Medical care; Medical laws and legislation; Medical policy; Unfair competition